Assessment For Management Potential: Scale Design and Development, Training Effects and Rater/Ratee Sex Effects - Norton, Steven D.; Gustafson, David P.; Foster, Charles E. (Academy of Management Journal, 1977)
Six behaviorally based bipolar scales were developed to assess management potential. Managers used these scales before and after training to rate male and female versions of cases describing two hypothetical job incumbents. Both means and variances of ratings were smaller after training. Rater/ratee sex effects were also studied.